EDUKASI LABELING BAGI PELAKU UMKM DI PROVINSI LAMPUNG - Husna, Nurul (COMMENT: Journal of Community Empowerment, 2023)
This article discusses the benefits of product labeling for MSME in the processed food sector. Labeling, as a key element in marketing, plays a crucial role in shaping brand image, increasing consumer confidence, and enhancing product competitiveness in the market. Product labeling can be an important instrument in creating added value to processed food MSME products, improving market access, and promoting sustainability. The PKM team together with BBPOM Bandar Lampung as an operational technical implementer in the field of drug and food control, which in this PKM acts as a partner, conducted education and assistance to 22 MSME players. This PKM aims to increase awareness of the importance of labeling MSME products so that later it can increase the competitiveness of MSMEs at the international level. Based on the results of the pre-test and post-test questionnaire evaluations given, there was a 30% increase.